The effects of pressure dependent constitutive model to simulate concrete structures failure under impact loads - Mokhatar, S. N.; Sonoda, Y.; Kamarudin, A. F.; Md Noh, M. S.; Tokumaru, S. (2017)
The main objective of this paper is to explore the effect of confining pressure in the compression and tension zone by simulating the behaviour of reinforced concrete/mortar structures subjected to the impact load. The analysis comprises the numerical simulation of the influences of high mass low speed impact weight dropping on concrete structures, where the analyses are incorporated with meshless method namely as Smoothed Particle Hydrodynamics (SPH) method. The derivation of the plastic stiffness matrix of Drucker-Prager (DP) that extended from Von-Mises (VM) yield criteria to simulate the concrete behaviour were presented in this paper. In which, the displacements for concrete/mortar structures are assumed to be infinitesimal. Furthermore, the influence of the different material model of DP and VM that used numerically for concrete and mortar structures are also discussed. Validation upon existing experimental test results is carried out to investigate the effect of confining pressure, it is found that VM criterion causes unreal impact failure (flexural cracking) of concrete structures.